2021
DOI: 10.1242/jeb.242140
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics and hydrodynamics analyses of swimming penguins: wing bending improves propulsion performance

Abstract: Penguins are adapted to underwater life and have excellent swimming abilities. Although previous motion analyses revealed their basic swimming characteristics, the details of the 3-D wing kinematics, wing deformation, and thrust generation mechanism of penguins are still largely unknown. In this study, we recorded the forward and horizontal swimming of gentoo penguins Pygoscelis papua at an aquarium with multiple underwater action cameras and then performed a 3-D motion analysis. We also conducted a series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 52 publications
(69 reference statements)
1
16
0
Order By: Relevance
“…Reducing the moment arm of the hydrodynamic force and the wing beat frequency cause the reduction of the force required in the flapping muscles. According to the quasi‐steady calculation of the hydrodynamic force of the wing in swimming penguins (Harada et al, 2021), the hydrodynamic force of the wing is about 0.50 times body mass, which is much smaller than the aerodynamic force of the wing in ‘ flap‐flight ’ birds, such as pigeons (~4 times body mass, Ros et al, 2011) and Pacific parrotlets (~2 times body mass, Lentink et al, 2015). Therefore, it is likely that ‘ wp‐diving ’ birds are not required to exert much larger force than ‘ flap‐flight ’ birds to flap the wings underwater.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the moment arm of the hydrodynamic force and the wing beat frequency cause the reduction of the force required in the flapping muscles. According to the quasi‐steady calculation of the hydrodynamic force of the wing in swimming penguins (Harada et al, 2021), the hydrodynamic force of the wing is about 0.50 times body mass, which is much smaller than the aerodynamic force of the wing in ‘ flap‐flight ’ birds, such as pigeons (~4 times body mass, Ros et al, 2011) and Pacific parrotlets (~2 times body mass, Lentink et al, 2015). Therefore, it is likely that ‘ wp‐diving ’ birds are not required to exert much larger force than ‘ flap‐flight ’ birds to flap the wings underwater.…”
Section: Discussionmentioning
confidence: 99%
“…However, the wing model that we fabricated for the previous study was a no sweepback wing, which means that the leading edge of the wing is set to be vertical to the longitudinal axis of the body. During our observations on the swimming of real penguins, it was found that the wings swept backward by a range from 24.6 • to 46.7 • relative to the forward direction [19]. This variation in the sweepback angle possibly affects the thrust and efficiency of the flapping-wing propulsion.…”
Section: Introductionmentioning
confidence: 87%
“…The cross-sectional profiles of the wing are obtained by scanning a real penguin wing and adjusting it to determine symmetric profiles along the thickness direction [20]. The details of the obtained profiles can be found in our previous paper [19]. According to our kinematic research on penguin swimming, the wing has an average sweepback angle of approximately 35 • relative to the feathering axis +Z W [19].…”
Section: Wing Mechanismmentioning
confidence: 99%
See 2 more Smart Citations